2017
DOI: 10.7589/2016-05-096
|View full text |Cite
|
Sign up to set email alerts
|

HEALTH SURVEY OF FREE-RANGING RACCOONS (PROCYON LOTOR) IN CENTRAL PARK, NEW YORK, NEW YORK, USA: IMPLICATIONS FOR HUMAN AND DOMESTIC ANIMAL HEALTH

Abstract: We conducted health assessments on 113 free-ranging raccoons ( Procyon lotor ) in Central Park, New York City, US, in February 2010, September 2010, and November 2011 in conjunction with a trap-vaccinate-release program to control a raccoon rabies epizootic. Five individuals were sampled at two time points for 118 raccoon examinations in total. We tested 13 of 13 and 8 of 13 euthanized raccoons for rabies and canine distemper virus (CDV), respectively, by antigen testing on brain tissue; all were negative for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…The overall prevalence of Campylobacter among raccoons sampled in our study was high (46.3%) in comparison with previous research examining free‐ranging raccoons in urban areas in Japan (1.3%) and New York City (6%; Lee et al., 2011; Rainwater et al., 2017). However, a similar prevalence was found among raccoons trapped on swine, beef and dairy farms in the same geographic region in 2010 (40.8%; Viswanathan et al., 2017a).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The overall prevalence of Campylobacter among raccoons sampled in our study was high (46.3%) in comparison with previous research examining free‐ranging raccoons in urban areas in Japan (1.3%) and New York City (6%; Lee et al., 2011; Rainwater et al., 2017). However, a similar prevalence was found among raccoons trapped on swine, beef and dairy farms in the same geographic region in 2010 (40.8%; Viswanathan et al., 2017a).…”
Section: Discussioncontrasting
confidence: 73%
“…Among wildlife species, wild birds have received the most attention as potential sources of Campylobacter in previous source attribution research (Greig et al., 2015); not only is Campylobacter widely recognized as a commensal organism in birds, but the highly mobile nature of birds may facilitate the transmission and dissemination of Campylobacter between different components of the ecosystem (Reed et al, 2003). Until recently, medium‐sized mammalian species such as raccoons ( Procyon lotor ) had received little attention in this area of research (Lee et al., 2011; Mutschall et al., 2020; Rainwater et al., 2017). Due to their prevalent populations within both urban and rural environments, and their propensity to interact with domestic animals and humans, raccoons may represent an important link in the epidemiology of Campylobacter within the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports from varying temperate zone urban, rural and natural environments have provided contradictory results as to the prevalence of Salmonella serovars in raccoons (Compton et al, ; Jardine et al, ; Lee et al, ; Rainwater et al, ; Very et al, ). In tropical urban settings, we found S. Hartford to have the highest prevalence followed by S. Typhimurium and S. Bovismorbificans.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, given the practical limitations imposed by potential delays in sample processing (3-11 days) due to shipping of fecal swabs from the study site (Guelph, Ontario) to the laboratory where microbiological work was carried out (Lethbridge, Alberta), it is very likely that our prevalence estimates underestimate true prevalence rates in this raccoon population. By contrast, studies from Japan and New York found only 1.3 and 6% of raccoons carried Campylobacter, respectively (32,44). There are a limited number of studies systematically examining Campylobacter in raccoons or other medium sized mammals.…”
Section: Discussionmentioning
confidence: 97%